“PELATIHAN PEMBUATAN KARTU DENGAN ORIGAMI MENGAMBIL TEMA HEWAN LANGKA INDONESIA” (RPTRA Dharma Suci- Jakarta) - Erlyana, Yana; Hidajat, Henny (Universitas Bunda Mulia, 2019)
Environmental education has a very important role in overcoming current environmental problems. The development of environmental awareness is increasingly important to continue to be socialized to all elements of society who have a responsibility in maintaining and preserving the environment for sustainability that is relevant to nature. Early childhood must begin to have an awareness of the importance of environmental aspects in maintaining life now and in the future because environmental education is the responsibility of the entire community, including government and educational institutions. This community service activity combines the provision of material on the importance of preserving the environment, especially Indonesian rare animals and development of children’s fine motor skill by using paper folding activities or commonly called origami. This study using collaborative and participatory action research methods (PAR). At the community service this time, the target of the participants was children aged 6-8 years in the North Jakarta Dharma Suci RPTRA environment. The results of the training from this activity showed that children tend to be enthusiastic in participating in giving the material given. Children tend to be interested in learning more about rare animals in Indonesia. And it can be seen that the children's fine motor skills, namely in folding paper (origami), seem to be better in several processes in the process of folding paper.